Embedding Organizational Culture Values towards Successful Business Continuity Management (BCM) Implementation - Mansol, NH; Alwi, NHM; Ismail, W (IEEE, 2024)
Today's increased reliance on Information and Communications Technology (ICT) has raised the expectations for service quality, reliability and availability. Such expectations have introduced BCM as a crucial requirement for organizations. BCM is a management process that helps in improving the organization's resilience to interruptions caused by information security threats. The implementation of BCM not only involves the information technology (IT) department, but also business areas that use IT services. BCM however, only receives attention with the support and direction from top management whenever it is required for regulatory compliance. Therefore this paper aims to explore and identify the effects of organizational culture on the successful implementation of BCM in Malaysian organizations. Quantitative surveys have been distributed to 300 participants with varying roles within the organizational hierarchy. 22 Malaysian IT organizations and departments have been selected to participate in the survey. The survey explores the organization employee's view on the importance and effect of organizational culture on BCM implementation. The results indicate that cultural factors greatly impact and play an important role to the organization in terms of BCM readiness and implementation. The results are useful as a guidance for organizations in Malaysia specifically to monitor security incidents or threats which may arise not only from technicalities but also human complexity. The results may also aid in the preparation of organizational guidelines regarding readiness towards BCM implementation.